2021
DOI: 10.1101/2021.03.12.435190
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Platelet transcriptome yields progressive markers in chronic myeloproliferative neoplasms and identifies putative targets of therapy

Abstract: Predicting disease natural history remains a particularly challenging endeavor in chronic degenerative disorders and cancer, thus limiting early detection, risk stratification, and preventive interventions. Here, profiling the spectrum of chronic myeloproliferative neoplasms (MPNs), as a model, we identify the blood platelet transcriptome as a generalizable strategy for highly sensitive progression biomarkers that also enable prediction via machine learning algorithms. Using RNA sequencing (RNA seq), we derive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 108 publications
(172 reference statements)
0
9
0
Order By: Relevance
“…Four candidate markers from our prior platelet RNA-seq analyses 20 were identified based on specific trends in progressive expression across the 3 MPN subtypes vis-à-vis healthy donors (FDR<0.01, n=120) independent of patient driver mutational status. ENKUR and CALR, in particular, were identified based on opposing trends in progressive expression (Figure 1A and Figure S1A), CDC20 on its specific high expression in MF patients alone in contrast with healthy donors and ET or PV patients (Figure 1A, top right), and CREB3L1 based on its substantially increased (> 50-fold) expression in all MPNs vs healthy (Figure S1A, top right).…”
Section: Validation Of Rna and Protein Expression Of 4 Mpn Candidate ...mentioning
confidence: 99%
See 1 more Smart Citation
“…Four candidate markers from our prior platelet RNA-seq analyses 20 were identified based on specific trends in progressive expression across the 3 MPN subtypes vis-à-vis healthy donors (FDR<0.01, n=120) independent of patient driver mutational status. ENKUR and CALR, in particular, were identified based on opposing trends in progressive expression (Figure 1A and Figure S1A), CDC20 on its specific high expression in MF patients alone in contrast with healthy donors and ET or PV patients (Figure 1A, top right), and CREB3L1 based on its substantially increased (> 50-fold) expression in all MPNs vs healthy (Figure S1A, top right).…”
Section: Validation Of Rna and Protein Expression Of 4 Mpn Candidate ...mentioning
confidence: 99%
“…However, this study was primarily in mice and remains to be confirmed in independent additional MPN models and patient-derived specimens. Our recent investigation, profiling the blood platelet transcriptome in all three subtypes of MPN patients 20 identified high expression of genes and pathways associated with impaired proteostasis, ER stress and unfolded protein response (UPR) well-recognized in other age-related disorders [21][22][23][24][25] . Here, we extend our prior MPN patient platelet transcriptomic data with a focus on genes associated with proteostasis, cell proliferation, ER stress or calcium signaling at high statistical significance (FDR <0.01), and representing four types of trends in platelet RNA expression across MPN subtypes: progressively downregulated, progressively upregulated, consistently upregulated, and uniquely upregulated in MF alone.…”
Section: Introductionmentioning
confidence: 99%
“…The ability to predict progression to advanced disease and likelihood of complications including thrombosis is crucial for optimal management. In this issue of Cell Reports Medicine , Shen and colleagues 1 demonstrate that the platelet transcriptome can differentiate between clinically distinct sub-types of myeloproliferative neoplasms (MPNs), a group of chronic blood cancers. They identify key features of the platelet transcriptome that, when combined with basic clinical predictors, can predict advanced stage disease.…”
Section: Main Textmentioning
confidence: 99%
“…Shen et al. 1 analyzed 120 purified platelet samples from healthy controls and two cohorts of patients with MPN (24 ET, 33 PV, and 40 primary or secondary MF), generating the largest dataset of platelet transcriptomes in MPNs reported to date. Each clinical subtype showed differential gene expression signatures as compared to healthy controls, with the most pronounced changes observed in MF (> 6600 differentially expressed genes).…”
Section: Main Textmentioning
confidence: 99%
See 1 more Smart Citation